The effects of a group exercise and education programme on symptoms and physical fitness in patients with fibromyalgia: a prospective observational cohort study. Issue 15 (17th July 2022) - Loftus, Nadia; Dobbin, Nick; Crampton, Jennifer Susan
Abstract: Purpose: Given the limited attention on a combined exercise and education approach for those with chronic musculoskeletal pain disorder such as fibromyalgia, the purpose of this was to evaluate the efficacy of a combined exercise and education programme on symptoms and physical fitness in participants with fibromyalgia. Materials and methods: Using a prospective observational cohort study, participants with fibromyalgia ( n  = 75) volunteered. The 6-minute-walk-test (6MWT) and revised-fibromyalgia-impact-questionnaire (FIQR) were used before, after (6 weeks) and 6-months post an exercise and education programme. Results: Forty-three participants (age = 49.7 ± 15.2 y) completed the 6-week programme, with improvements observed for the 6MWT (67 m, p  < 0.001) and FIQR (11 AU, p  < 0.001), though only two (6MWT) and five (FIQR) participants, respectively, achieved the minimal clinically important difference (MCID). Using 74% of the intial sample, a small-to-moderate improvement in scores were observed across the 6-month period for the 6MWT (37 m, p  = 0.002) and FIQR (3 AU, p  = 0.01), with only two participants achieving the MCID for the 6MWT. Conclusions: The results in this study indiciate small-to-moderate improvements in the 6MWT and FIQR after a combined exercise and education programme, with direct delivery being more effective. Implications for rehabilitation: A six-week exercise and education programme elicited moderate, short-term (6 weeks) benefits on physical fitness and key symptoms in patients with fibromyalgia. On average, these benefits were sustained in the long-term (6 months) following the programme but were small-to-moderate and lower than the MCID. Regular follow-up may be required to improve adherence to the education and exercise programme and maintain or increase the observed improvements in 6MWT and FIQR.